THE CLIMATERIC SYNDROME IN WOMEN’S LIVES - Messias Santos Silva, Manoel (Health and Society, 2023)
Menopause is the subject of myths and misunderstanding and also a comprehensive period of female life, characterized by metabolic and hormonal changes that bring involving the psychosocial context. Its symptomatology is not universal, but varies according to factors that determine the way of how these symptoms are noticed. For the present work, we performed a literature search in databases of scientific articles, in addition to books and periodicals relevant to the topic, seeking information about menopause and the perception of women in this life cycle. Aiming to improve care for women in this new phase of life, it becomes relevant research in relation to the theme groups and the implementation of the Family Health Program in order to meet climacteric women holistically, addressing emotional, biological and social their health, giving priority to prevention and health promotion and consequently to improve the quality of life through exchanges of experiences and the questioning of concepts and acquisition of new knowledge.